2015
DOI: 10.1007/s00595-015-1214-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inappropriate lymphadenectomy on lung metastasectomy for patients with metastatic colorectal cancer

Abstract: The presence of LNM and uLNs is associated with an increased risk of death. The association of nodal assessment at the time of metastasectomy to identify LNM helps us to refine the postoperative prognosis; therefore, its impact should be properly studied in a prospective clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
16
0
6
Order By: Relevance
“…Diese Einschlusskriterien sollten sicherstellen, dass sowohl dem medizinischen Fortschritt in den Bereichen perioperatives Management sowie (neo)adjuvante Therapien Rechnung getragen wird, als auch ein Abbild von der Lungenmetastasenchirurgie in erfahrenen, thoraxchirurgischen Zentren vermittelt werden kann. Nach schrittweiser Durchsicht von 1224 Titeln, Zusammenfassungen und 80 Volltexten erfüllten 18 Veröffentlichungen die Einschlusskriterien [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Hiervon entfallen 6 Publikationen [7][8][9][10][11][12] auf Berichte des spanischen GECMP-CCR Studienregisters und 2 Veröffentlichungen [16,17] auf die Beschreibung einer japanischen Kohorte.…”
Section: Methodenunclassified
“…Diese Einschlusskriterien sollten sicherstellen, dass sowohl dem medizinischen Fortschritt in den Bereichen perioperatives Management sowie (neo)adjuvante Therapien Rechnung getragen wird, als auch ein Abbild von der Lungenmetastasenchirurgie in erfahrenen, thoraxchirurgischen Zentren vermittelt werden kann. Nach schrittweiser Durchsicht von 1224 Titeln, Zusammenfassungen und 80 Volltexten erfüllten 18 Veröffentlichungen die Einschlusskriterien [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Hiervon entfallen 6 Publikationen [7][8][9][10][11][12] auf Berichte des spanischen GECMP-CCR Studienregisters und 2 Veröffentlichungen [16,17] auf die Beschreibung einer japanischen Kohorte.…”
Section: Methodenunclassified
“…The pathological identification of lymph node involvement may be as high as 44% when radical mediastinal lymphadenectomy is routinely performed . Several authors advocate for the routine performance of mediastinal lymph node evaluation to provide better prognostic information, as the therapeutic effect of removal of these nodes is unknown . An analysis of 522 patients from 32 thoracic surgery departments in Spain undergoing first lung metastasectomy for CRC identified that lymph node assessment was performed in 48% of cases and nodal metastases were identified in 10% of those patients, with 20% having systematic nodal dissection, 35% having systematic nodal sampling, and 45% having minor lymphadenectomy .…”
Section: Lymph Node Sampling/dissectionmentioning
confidence: 99%
“…33 Several authors advocate for the routine performance of mediastinal lymph node evaluation to provide better prognostic information, as the therapeutic effect of removal of these nodes is unknown. 6,23,24,40,45,47 An analysis of 522 patients from 32 thoracic surgery departments in Spain undergoing first lung metastasectomy for CRC identified that lymph node assessment was performed in 48% of cases and nodal metastases were identified in 10% of those patients, with 20% having systematic nodal dissection, 35% having systematic nodal sampling, and 45% having minor lymphadenectomy. 47 5-year disease-specific survival was 58% in those without nodal metastases, 24% in those with nodal metastases, and 44% in those with unknown lymph node status (P = 0.006).…”
Section: Lymph Node Sampling/dissectionmentioning
confidence: 99%
“…Median survivals for the no lymph node dissection group, negative lymph node group, and positive lymph node group were 52, 58.5, and 34 months, respectively (21). In the Spanish prospective registry of CRC PM, lymph node dissection was realized in 48% of patients with 10% of lymph node involvement (22). The 5-year survival was best for patients with negative lymph node invasion, worst for those with positive lymph node invasion, and in-between for those with unknown lymph node status because they were not resected.…”
Section: Mediastinal Lymph Node Dissectionmentioning
confidence: 99%